2021
DOI: 10.3390/polym13101568
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of a Tubular Model of Human Urothelial Mucosa Using Human Wharton Jelly Mesenchymal Stromal Cells

Abstract: Several models of bioartificial human urothelial mucosa (UM) have been described recently. In this study, we generated novel tubularized UM substitutes using alternative sources of cells. Nanostructured fibrin–agarose biomaterials containing fibroblasts isolated from the human ureter were used as stroma substitutes. Then, human Wharton jelly mesenchymal stromal cells (HWJSC) were used to generate an epithelial-like layer on top. Three differentiation media were used for 7 and 14 days. Results showed that the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To promote attachment, cells were resuspended in a minimal amount of medium (50 µL) and DLs were immobilized using agarose casts, as previously reported [38]. In order to induce epithelial differentiation of both cell types seeded on the RL, these tissues were cultured for 21 days in EM epithelial differentiation medium containing epithelial growth and differentiation factors, as previously described [39]. The EM medium consisted of a mixture of 150 mL of HAM-F12, 300 mL of DMEM, 50 mL of fetal bovine serum, 1% antibiotics/antimycotics, 24 µg/mL of adenine, 5 µg/mL of insulin, 1.3 ng/mL of triiodothyronine, 0.4 µg/mL of hydrocortisone, and 10 ng/mL of EGF (epidermal growth factor) (all of them, from Merck).…”
Section: Generation Of Recellularized Limbal Substitutes By Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…To promote attachment, cells were resuspended in a minimal amount of medium (50 µL) and DLs were immobilized using agarose casts, as previously reported [38]. In order to induce epithelial differentiation of both cell types seeded on the RL, these tissues were cultured for 21 days in EM epithelial differentiation medium containing epithelial growth and differentiation factors, as previously described [39]. The EM medium consisted of a mixture of 150 mL of HAM-F12, 300 mL of DMEM, 50 mL of fetal bovine serum, 1% antibiotics/antimycotics, 24 µg/mL of adenine, 5 µg/mL of insulin, 1.3 ng/mL of triiodothyronine, 0.4 µg/mL of hydrocortisone, and 10 ng/mL of EGF (epidermal growth factor) (all of them, from Merck).…”
Section: Generation Of Recellularized Limbal Substitutes By Tissue Engineeringmentioning
confidence: 99%
“…For the immunohistochemical analyses, results were semiquantitatively categorized as strongly positive signal (+++), positive signal (++), slightly positive signal (+), or negative signal (−), as previously reported [39].…”
Section: Quantitative Analysis and Statisticsmentioning
confidence: 99%
“…In this regard, our research group previously demonstrated the potential usefulness of HWJSC to generate epithelial-like cell layers in several models of bioengineered human tissues, including the urothelial mucosa ( Garzón et al, 2021 ), the skin epidermis ( Martin-Piedra et al, 2019 ), oral mucosa epithelium ( Alfonso-Rodríguez et al, 2015 ) and also the corneal epithelium ( Garzón et al, 2014 ). In the case of the human cornea, the use of HWJSC were able to stratify and differentiate very efficiently on a bioartificial corneal stroma, especially when the bioengineered corneas were grafted in vivo ( Garzón et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To generate primary cell cultures of human MSC, we obtained samples of human adipose tissue, dental pulp, and umbilical cord according to previously described protocols 19 21 . Samples corresponding to three different donors were used (n = 3 for each tissue).…”
Section: Methodsmentioning
confidence: 99%
“…hADSC and hDPSC were cultured in Dulbecco’s Modified Eagle’s Medium (DMEM) (Sigma-Aldrich/Merck, Burlington, MA, USA) supplemented with 10% fetal bovine serum (FBS) and 1% antibiotics and antimycotics (100 U/mL penicillin G, 100 mg/mL streptomycin, and 0.25 mg/mL amphotericin B) (Sigma-Aldrich/Merck). hWJSC were cultured in Amniomax-C100 culture medium (Gibco-Thermo Fisher Scientific) 21 23 . In all cases, cells were kept under standard cell culture conditions at 37 °C in a humidified incubator (Esco Lifesciences Group, Singapore, Singapore) with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%